Redemption by a Renewed Creation in Christ According to the “Gaudium Et Spes” - Sowa, Władysław (Studia Theologica Varsaviensia, 2020)
Analysing the whole process of the development of the doctrine of redemption in Gaudium et Spes, we can conclude that the Council responded to the demands expressed before the beginning of the doctrine. It remained faithful to the teachings of St omas Aquinas, while preserving the essential content of his doctrine, although it expressed it in a new language. e Council was able to positively explain the doctrine of the mystery of redemption, without arguing with various contemporary theological tendencies. Redemption is shown as the work of Jesus Christ through His salvific Incarnation and the redemptive paschal mystery of death, resurrection, ascension and exile of the Holy Spirit. Redemption freed man from the bondage of Satan and sin, became a new covenant with the Father, reconciled delusions with God and with himself, merited life and revealed the mystery of love. Redemption is a great event in the history of salvation, which begins with the work of Creation. From the history of the various editions of Gaudium et Spes, from the interventions of the Council Fathers and from the solutions to the theological problems relating to the whole reality of the modern world, we can conclude that the Pastoral Constitution on the Church points to the relationship between creation and redemption, speaking of creation in the perspective of redemption and defining redemption as the renewal of creation in Christ.